ETIKA PENYELESAIAN KONFLIK DALAM PENTADBIRAN ISLAM: SUATU PERBANDINGAN - Syed Ismail, Sharifah Hayaati (Jurnal Syariah, 2019)
Conflict is a phenomenon that can happen anywhere, anytime. It can gives positive as well as negative impact to human relations and organisational development. Many people see conflict as a negative situation of human relations but not many is prepared to resolve it in a positive and strategic manner particularly in an organisation. Islam as a way of life has underlined guides and rules in managing and preventing conflicts from occur. Thus, this article is concentrating on defining as well as exploring several topics on conflict including its concept, cause and forms and ethics in resolving conflicts both from an Islamic and modern perspectives. It is hoped that with this explanation people in an organisation will be more positive in dealing with any forms of conflict.